Corporate Communication: A Guide to Theory and Practice - Cornelissen, Joep P. (SAGE Publications, 2020)
The latest edition of Corporate Communication has been fully revised by the author to reflect new trends and developments in social media and to capture emergent topics like CEO activism and corporate character. It remains essential reading for students studying Corporate Comms as well as Organizational , Strategic , PR and Marketing Communications.